Comparison of Microleakage under Rebonded Stainless Steel Orthodontic Brackets Using Two Methods of Adhesive Removal: Sandblast and Laser. - Mohamad Hossein Tudehzaeim; Soghra Yassaei; Shohreh Taherimoghadam (Tehran University of Medical Sciences, 2015)
Debonding is a common occurrence in orthodontic treatment and a considerable number of orthodontists prefer to rebond the detached brackets because of economic issues. The aim of this study was to compare the microleakage beneath rebonded stainless steel brackets using two methods of adhesive removal namely sandblast and laser.Sixty human premolar teeth were randomly divided into three groups. Following bonding the brackets, group 1 served as the control group. Brackets in groups 2 and 3 were debonded, and adhesive removal from the bracket bases was done by means of sandblasting and Er-YAG laser, respectively. After rebonding, teeth in each group were stained with 2% methylene blue for 24 hours, sectioned and examined under a stereomicroscope. Marginal microleakage at the adhesive-enamel and bracket-adhesive interfaces in the occlusal and gingival margins was determined. Statistical analysis was done using the Kruskal-Wallis test.Comparison of the microleakage scores among the three groups revealed no statistically significant difference (P > 0.05). At the enamel-adhesive interface, the gingival margins in all groups showed higher microleakage while in the adhesive-bracket interface, the occlusal margin exhibited greater microleakage.Er-YAG laser irradiation and sandblasting for adhesive removal from the debonded brackets yielded clinically acceptable microleakage scores.